Que Província, Autonomia ou Autarquia Supramunicipal face à Crise Político-Militar no Exclave de Cabinda? - Almeida, E. C. (Associação CEDESA - Angola Research Nertwork, 2025)
The lack of political and administrative autonomy, along with the political-military crisis involving separatist movements, such as the Front for the Liberation of the Enclave of Cabinda (FLEC) and its armed wing, FLEC-Armed Forces of Cabinda (FLEC-FAC), has been a significant challenge for the local population. Recently, based on a possible proposed Law on Cabinda to be presented by UNITA, FLEC-FAC announced a ceasefire until June 14, 2025 – although the Angolan Government has already denied these reports – offering an opportunity for dialogue and a search for a peaceful solution.